From Yellow to Blue: Exploring Lance Armstrong's Image Repair Strategies Across Traditional and Social Media. (June 2015) - Hambrick, Marion E.; Frederick, Evan L.; Sanderson, Jimmy
This research explored how Lance Armstrong utilized image repair strategies during 2012 and early 2013. This time frame represented a turbulent period in his career, as he faced a doping investigation by the U.S. government and later admitted to using performance-enhancing drugs during a nationally televised interview with Oprah Winfrey. Armstrong's 859 tweets during this time period and his comments during the Oprah Winfrey interview were collected and subjected to a thematic analysis using Benoit's image repair typology. Results indicated that via Twitter, Armstrong used attacking the accuser, bolstering, and stonewalling strategies but during the interview demonstrated contrition by employing mortification, shifting blame, simple denial, provocation, and victimization along with two newly identified strategies: conforming and retrospective regret. The results suggest that athletes who display multifaceted image repair strategies can embolden identification and attachment with followers and introduce competing media narratives surrounding their identity. However, these strategies may backfire when divergent messages are delivered in different media forums. Theoretical and practical implications will be discussed.